Unraveling the link: locomotor activity exerts a dual role in predicting Achilles tendon healing and boosting regeneration in mice - Faydaver, Melisa; El Khatib, Mohammad; Russo, Valentina; Rigamonti, Mara; Raspa, Marcello; Di Giacinto, Oriana; Berardinelli, Paolo; Mauro, Annunziata; Scavizzi, Ferdinando; Bonaventura, Fabrizio; Mastrorilli, Valentina; Valbonetti, Luca; et al. (Frontiers in Veterinary Science, 2023)
Tendon disorders present significant challenges in the realm of musculoskeletal diseases, affecting locomotor activity and causing pain. Current treatments often fall short of achieving complete functional recovery of the tendon. It is crucial to explore, in preclinical research, the pathways governing the loss of tissue homeostasis and its regeneration. In this context, this study aimed to establish a correlation between unbiased locomotor activity pattern of CRL:CD1(ICR) mice exposed to uni-or bilateral Achilles tendon (AT) experimental injuries and the key histomorphometric parameters that influence tissue microarchitecture recovery. The study involved the phenotyping of spontaneous and voluntary locomotor activity patterns in male mice using Digital Ventilated Cages (DVC®) with access to running wheels, either granted or blocked. The mice underwent non-intrusive 24/7 long-term activity monitoring for the entire study period. This period included 7 days of pre-injury habituation followed by 28 days post-injury. The results revealed significant variations in activity levels based on the type of tendon injury and access to running wheels. Notably, mice with bilateral lesions and unrestricted wheel access exhibited significantly higher activity after surgery. Extracellular matrix (ECM) remodeling, including COL1 deposition and organization, blood vessels remodeling, and metaplasia, and cytological tendon parameters, such as cell alignment and angle deviation were enhanced in surgical (bilateral lesion) and husbandry (free access to wheels) groups. Interestingly, correlation matrix analysis uncovered a strong relationship between locomotion and microarchitecture recovery (cell alignment and angle deviation) during tendon healing. Overall, this study highlights the Activity-Driven Tendon Microarchitecture Recovery 2 This is a provisional file, not the final typeset article potential of using mice activity metrics obtained from a home-cage monitoring system to predict tendon microarchitecture recovery at both cellular and ECM levels. This provides a scalable experimental setup to address the challenging topic of tendon regeneration using an innovative and animal welfarecompliant strategies.